Administration of Etanol White Turmeric (Curcuma zedoaria) Extracts Increased Superoxide Dismutase (SOD) And Decreased Malondialdehide (MDA) In Cigarette Smoke-Exposed Male Mice (Mus musculus) Strain Balb/C - Yuliana Tjua; Ida Sri Iswari; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Background: Cigarette smoke is free radical which decrease superoxide dismutase (SOD) and increased malondialdehyde (MDA) levels. Etanol white turmeric (Curcuma zedoaria) extract contains flavonoids, polyphenols, tannins, and antioxidant activity. This study aimed to prove white turmeric increased SOD and decreased MDA in cigarette smoke-exposed male mice (Mus musculus) strain Balb/c. Methods: This study used a randomized pre-test and post-test control group design. The subjects were 12 male mice and divided into two groups (n = 6). The control group was exposed to cigarette smoke 1 stick/day and given aquadest 1 ml as a placebo. The treatment group was exposed to cigarette smoke 1 stick/day and given white turmeric extract of 4 mg/20gram BW in one-hour cigarette smoke exposure. The blood was drawn through canthus medial sinus orbital to examine the level of SOD by ELISA and MDA level by TBARS method. Results: There was no significant differences in SOD levels (p = 0.930) and MDA levels (p= 0.984) between groups in pre-test. However, the mean SOD levels (p <0.001) and MDA levels (p<0.001) between groups were significant in post-test. In control group, there was no change in SOD (from 0.555±0.156 to 0.595±0.233 ng/mL; p = 0.650) and MDA (from 14.3±0.614 to 14.3±0.513 μM; p = 0.958). In contrast, the treatment group has increase SOD (from 0.565±0.273 to 2.28±0.110 ng/mL; p <0.001) and decrease MDA (from 14.3±0.931 to 5.78±1.06 μM; p <0.001). Conclusion: Administration of Etanol white turmeric extracts increased SOD and decreased MDA in cigarette smoke-exposed male mice strain Balb/c.